POWER DEVELOPMENT IN THE STARTING PHASE OF SPEED RUNNING - JURJIU, Nicolae-Adrian; PUTA, Tiberiu; PUTA, Carla; GLAZER , Ciprian (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
Introduction: Short distance running is part of the maximum intensity cycling exercises, consisting of combined efforts, each step being performed as a result of a complete impulse, characterized by covering a certain distance in a shorter time. Objective: This study aims to follow the development of power for the start in short distance speed trials. Material and method: A 26-year-old male athlete, who has been practicing athletics for 14 years, participated in the study, based on the 100-meter flat sprint. The pre-test was performed before the preparation period, the intermediate test after one, two and three mesocycles (months) and the final test after the fourth mesocycle (after 4 months). The evaluations followed the strength with which 4 exercises were performed (deadlift, clean, power clean and squat) of 6 repetitions each. At the same time, the length of the distance covered in the first three steps from the start was followed. During the four mesocycles, the athlete participated in specific strength development training. Results: Following the training program for the development of lower limb power, execution speed and lower limb strength, statistically significant results were observed in 2 of the 4 exercises performed in the evaluations. Regarding the jumped step starting from the two different positions, an evolution was observed reaching from the length of 5.24m to 6.44m in the first variant, and from 5.31m to 5.93m in the second variant. In both cases, the execution time of the three steps increased, reaching the value of 1.85s, respectively 1.49s. Conclusions: Following the results obtained in the five evaluations, we notice that the training program was developed efficiently and that the results improved in most of the evaluation tests.